PERBANDINGAN MULTI FACTOR BOBOT EVALUASI PROCESS DAN SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE DALAM PEMBUDIDAYAAN BIBIT BUNCIS - Muhammad Hari Ramadhan; Yusfrizal Yusfrizal (Jurnal Informatika Kaputama (JIK), 2020)
To increase bean production, bean seedlings have an important role in its cultivation. The use of superior seeds is one of the factors that influence the productivity of chickpea farmers. The presence of bean seeds at any time causes farmers to plant on time. Problems that often arise in the process of selecting bean seed systems include farmers needing a long time in determining the type of bean seeds because they have to choose manually with the criteria needed to determine the type of bean seeds desired and farmers also have not used a scientific way to choose the type bean seeds so that sometimes the results obtained are not as expected. Then it is necessary to develop a computer application as an alternative decision making that is used quickly and accurately. One of them is the Decision Support application that helps users to determine the decision quickly, precisely and accurately. This system is designed with the Multi Factor Bobot Evaluasi Process method which aims to determine decisions subjectively and intuitively by considering several factors that affect alternatives. Therefore the Decision Support application with the Multi Factor Bobot Evaluasi Process method and SMART can be to alternative for the decision maker to determine the bean seeds.